Effect of the Clenbuterol drug in some physiological parameters in male rabbits(Oryctolagus cuniculs) - Baghdad Science Journal (مجلة بغداد للعلوم, 2016)
This study was designed to investigate the effect of the Clenbuterol drug in some physiological parameters of Liver, Kidney function and lipidprofie concentration. Fourty adult male rabbits were used in this study. The animals were randomly divided into four groups,the first group was given distilled water (control) ,while the other third groups were given (2,4,6 µg/kg) of Clenbuterol drug for 30 days. Blood samples were collected after 14 and 30 days of the treatment for biochemical study. Drug caused non significant increase(P